Surgical Outcome of Occipitocervical Fixation for Craniocervical Instability - Amir, Sohail; Ayub, Shahid (Journal of Gandhara Medical and Dental Science, 2023)
OBJECTIVES To evaluate the efficacy of Occipitocervical Fixation (OCF) in patients with craniocervical instability in two tertiary care hospitals. METHODOLOGY This retrospective case series study was conducted at Hayatabad Medical Complex, Peshawar, from April 2017 to December 2020. A non-probability sampling technique was used, and size was calculated via online software with a 95 % confidence level and 5% margin of error. All patients with craniocervical instability were included in our study, and those having occipital bone fractures or previously operated patients with the same technique were excluded from the study. The Nurick score was used to assess neurological function pre-and postoperatively. The demographic details of the patients, clinical features, radiographic findings (pre- and postoperative), and clinical outcomes using the Nurick myelopathy grading system were noted and entered into a structured proforma. All data were entered into SPSS Version 18 and analyzed. The results were presented in tables and pictures. RESULTS A total of 26 cases with craniocervical instability underwent OCF. The mean age of the patients was 40.5 + 1.2 SD years. There were 10 male patients and 16 female patients. The majority of patients showed improvements in myelopathic symptoms after the operation. The mean preoperative Nurick score was 3.0. At the end of follow-up after surgery, the mean Nurick score was 2.1. There was a total of 7(14.28%) cases having complications, of which 4 (8.16%) patients had wound infection, 2 (4.08%) patients had implant failure, and 1(2.04%) had vertebral artery injury. However, no postoperative neurological deficit was observed. CONCLUSION Occipitocervical fixation is a reasonable option to have spinal stability, achieve bone fusion and get neurological improvement. Certain conditions complicate the procedure, but experienced hands can safely handle these.